Recruitment of neutrophils by granulocyte colony-stimulating factor in cancer patients undergoing immunotherapy: the good, the bad, and the unknown - Krykbaeva, Irina; Rupani, Karishma Vijay; Liu, Johnson M. (Frontiers in Immunology, 2026)
Granulocyte-colony stimulating factor (G-CSF) is a cornerstone of supportive care in oncology, widely used to prevent chemotherapy-induced neutropenia and maintain dose intensity and treatment schedule. While G-CSF has been shown to be safe and effective in the context of chemotherapy, its effects in patients receiving chemo-immunotherapy with immune checkpoint inhibitors (ICIs) are less clear. There is a growing body of preclinical data to suggest that G-CSF negatively impacts the tumor microenvironment in mice and may contribute to tumor growth and metastasis. Consequently, as chemo-immunotherapy regimens have become standard across solid malignancies, the immunologic consequences of G-CSF in this setting have come under renewed scrutiny. G-CSF is a pleiotropic cytokine, and one of its most prominent functions is to stimulate the proliferation and survival of neutrophils, which in the tumor microenvironment may exert both anti- and pro-tumorigenic roles. G-CSF stimulated neutrophils have been shown to contribute to the anti-tumor immune response via upregulation of unconventional T cells, maintenance of interferon gamma- based immunity, and direct tumor cell killing in some models. Other models, however, have shown that cytokine mixes containing G-CSF can polarize neutrophils towards a pro-tumorigenic state, promoting suppression of CD8+ T cells, creating an immunosuppressive cytokine milieu, and increasing metastatic potential. Ultimately, its effects appear to be dependent on the underlying immune state and composition of the tumor microenvironment. While preclinical data suggest that G-CSF may be blunting the efficacy of checkpoint blockade via its modulation of the neutrophil compartment in specific models, clinical data in the immunotherapy era remain limited and largely retrospective. Studies done primarily in lung cancer patients showed neither a clear survival benefit nor an increased mortality risk. In this review, we synthesize the preclinical and clinical literature examining G-CSF in solid tumor oncology, with a focus on its interaction with neutrophils and immune checkpoint inhibition. We highlight key mechanistic insights, emerging clinical signals, gaps in evidence, and ultimately emphasize the importance of adhering to strict, consensus guideline-based use of G-CSF during chemo-immunotherapy.